Bio-inspired chameleon technique in MAC protocol for energy efficient wireless sensor networks / \c Alaa Kamal Yousif Dafhalla. - Dafhalla, Alaa Kamal Yousif (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2018)
The objectives of this thesis are as follows ; to propose Bio-inspired Chameleon mechanism with Berkeley MAC (B-MAC) protocol that deals efficiency with the resource constrained and dynamic WSN ; to optimize B-MAC protocol using Taguchi method (TM) for single objective and differential evolution algorithm (DEA) for multi objectives ; to evaluate the impact of number of nodes, packet size, and mobility type with different scenarios and its relation with B-MAC protocol parameters on the performances of WSN.